Conceptual Model of Reintegration of Ukrainian Displaced Universities: Peacebuilding in Higher Education - Terepyshchyi, Serhii; Khomenko, Gleb (Studia Warmińskie, 2019)
The main functions of a higher education institution in the society of the 21st century are the dissemination of knowledge, the production of scientific research activities, international cooperation, the development and implementation of innovations, the development of human capital, the enhancement of moral values, the harmonious formation of personality based on humanistic ideas, etc. Carrying out these functions, higher education has an accentuated effect on the human mind, changing its attitude to the world around it. Today, obtaining a higher education is important not only in the context of the prospect of successful employment, but also in the context of the development of personal thinking.